Violation of the Ethical Principle of Patient Autonomy in Pandemics - Andrzej Augustyn; Piotr Adamik; Emilia Weaver (International Journal of Ethics and Society)
Introduction: Independence or autonomy is one of the fundamental rights of patients, which must be observed by health activists in all medical interventions and diagnostic and treatment measures. Considering the importance of patient autonomy in the field of health, the present study examines the violation of this ethical principle during pandemics. Material and Methods: The present study is a review study in which the researcher examined the articles related to the keywords of the present study that were published in Google Scholar, PubMed, Science Direct and Springer databases from 2015 to 2023. Conclusion: In the conditions of spread of the disease, the health system is forced to violate the principle of patients' autonomy in order to fulfill its moral and legal duty in protecting the health of the society. Although it seems that violating the principle of respecting the patient's right to autonomy in the conditions of spreading the disease is morally justified. However, completely ignoring this right and arbitrarily restricting it without citing sufficient evidence, in addition to violating the basic rights of the patient, has also damaged the public trust and social capital of the health system. And this institution will face problems in achieving its big goals and attracting people's participation.